Role Stress, Personality Type, Burnout, and Performance of Midwives towards Postnatal Care Program Achievement in Surabaya City - Halimsetiono, Elita; Rochmah, Thinni Nurul; Suminar, Dewi Retno (UI Scholars Hub, 2018)
The coverage of postnatal care program in Surabaya City had declined since 2011–2013 and could not reach the target. This analytic observational study used a cross-sectional design and was conducted during April–May 2015 to analyze the effect of role stress, personality type, and burnout on midwives’ performance towards postnatal care program achievement in Surabaya City. A total sample of 45 midwives was collected from eight primary health care centers in Surabaya City with basic emergency obstetric and neonatal care services. Accidental sampling was used for sample selection. This study indicated that most of the midwives were aged 20–30 years and had an diploma level of education in midwifery. Majority of them were married and were predominantly contract workers with However, majority of them had mild burnout and showed medium performance level. There was no influence of demographic characteristics, role stress, and personality type on burnout, whereas the performance was affected by role stress and personality type. The midwives’ performance was more influenced by personality type than by role stress.